Gene identification and transcriptome analysis of cadmium stress in tomato - Chen, Liang; Wu, Man; Jin, Wei; Lei, Ting; Li, Ying; Wu, Xuan; Fu, Shan (Frontiers in Sustainable Food Systems, 2023)
Cadmium (Cd) is a highly toxic heavy metal that can severely hinder plant growth and development.Tomato is one of the most important economicall crops in the world, and its quality and safety are closely related to human health. Therefore, it is important to elucidate the molecular mechanisms involved in tomato plant responses to Cd stress. In this study, tomato plants were treated with or without 100 μM Cd 2+ in hydroponic culture for 3 d. Transcriptional changes in tomato roots and shoots were examined by transcriptome sequencing techniques. A total of 1123 differentially expressed genes (DEGs) were identified in roots and 159 DEGs were identified in shoots after Cd treatment, including 15 DEGs were up-regulated and 24 DEGs were down-regulated in both roots and shoots. KEGG enrichment analysis showed that DEGs in the roots and shoots under Cd stress were significantly enriched in the glutathione metabolism pathway, sulfur metabolism pathway, phenylpropanoid biosynthesis, plant-pathogen interaction cutin pathway, suberine and wax biosynthesis pathway, and photosynthesis-antenna proteins pathway. 15 DEGs were further validated by quantitative real-time RT-PCR, including ABC transporter genes, WRKY transcription factors, and NAC transcription factors, among others. This study will provide a theoretical basis for further research on the molecular mechanisms involved in tomato responses to Cd stress, and genetic improvement of Cd tolerance.